2017
DOI: 10.1002/app.45554
|View full text |Cite
|
Sign up to set email alerts
|

Solid polymer electrolyte based on waterborne polyurethane for all‐solid‐state lithium ion batteries

Abstract: A series of solid polymer electrolytes (SPEs) based on comb-like nonionic waterborne polyurethane (NWPU) and LiClO 4 are fabricated via a solvent free process. The NWPU-based SPEs have sufficient mechanical strength which is beneficial to their dimensional stability. Differential scanning calorimetry analysis indicates that the phase separation occurs by the addition of the lithium salt. Scanning electron microscopy and X-ray diffraction analyses illustrate the good compatibility between LiClO 4 and NWPU. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…Due to this unique structure, WPU has been identified as a potential candidate polymer matrix for solid polymer electrolytes (SPEs) recently [ 10 ]. Bao et al prepared comb-like nonionic WPU based SPEs with ionic conductivity reaching 5.44 × 10 −6 S·cm −1 when the electrolyte contained 15 wt% LiClO 4 at 40 °C and SPE15 possessed a wide electrochemical stability window of 0–5 V (vs. Li+/Li) and thermal stability at 140 °C [ 11 ]. Ren et al reported a WPU as SPE, exhibiting an ionic conductivity of 5.14 × 10 −5 S·cm −1 at 25 °C with the addition of LiTFSI and all-solid-state LiFePO 4 /SPE/Li battery based on WPU12-20%Li delivered discharge specific capacities of 159 and 162 mAh·g −1 under 60 and 80 °C at 0.1 C, respectively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to this unique structure, WPU has been identified as a potential candidate polymer matrix for solid polymer electrolytes (SPEs) recently [ 10 ]. Bao et al prepared comb-like nonionic WPU based SPEs with ionic conductivity reaching 5.44 × 10 −6 S·cm −1 when the electrolyte contained 15 wt% LiClO 4 at 40 °C and SPE15 possessed a wide electrochemical stability window of 0–5 V (vs. Li+/Li) and thermal stability at 140 °C [ 11 ]. Ren et al reported a WPU as SPE, exhibiting an ionic conductivity of 5.14 × 10 −5 S·cm −1 at 25 °C with the addition of LiTFSI and all-solid-state LiFePO 4 /SPE/Li battery based on WPU12-20%Li delivered discharge specific capacities of 159 and 162 mAh·g −1 under 60 and 80 °C at 0.1 C, respectively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nonionic WBPU and WBPUU dispersions, which are based on the use of hydrophilic internal emulsifiers, e.g., polyethylene oxide, or lateral/terminal ether moieties [ 17 ], were not so widespread as the ionic counterparts, partly due to the weaker hydrophilic character of the nonionic emulsifiers, which difficult the dispersion in water. Nevertheless, due to their lower toxicity, better electrolyte stability, and resistance to shearing at low temperature, nonionic dispersions are the most suitable WBPU and WBPUU formulations for breathable coating applications, dyeing, finishing, and cosmetics, among others [ 23 , 48 , 49 ]. The ionic (anionic and cationic) dispersions are more widespread and extensively used in diverse applications, including adhesives, textiles, coatings, automotive topcoats or packaging films [ 50 ].…”
Section: A Step Beyond Conventional Internal Emulsifiersmentioning
confidence: 99%
“…Nowadays, lithium batteries are widely used for energy storage devices in smart phones, tablets/laptops, electric vehicles, etc. [1,2]. However, fire and explosion accidents of lithium batteries have occasionally occurred worldwide, some of which caused serious threats to user's health [3][4][5].…”
Section: Introductionmentioning
confidence: 99%